THE LOWER CAMBRIAN BOUNDARY IN INNER AREAS OF THE NORTH SIBERIAN PLATFORM - Khomentovskii V.V.; Karlova G.A.; Fedorov A.B. (My University, 1998)
The Vendian-Cambrian sequences recovered by boreholes K-203 and K-204 and by the deep Eiik Hole 343-0 in the North Siberian platform yielded abundant small-shelled fossils characteristic of the N. sunnaginicus Zone of the Tommotian Stage and also of P. antiqua and A. trisulcatus zones of the Nemakit-Daldynian Stage. These sequences appear to be more fossiliferous than the coeval sequence of the reference Markha borehole, which is used for the correlation of natural exposures in the northern part of Siberia with the borehole sections in its inner part. New data enable us to use the recognized stratigraphic subdivisions in the inner oil-and-gas provinces of the Siberian platform and to outline the elaboration method of the general stratigraphic scale for the Vendian-Cambrian boundary beds.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская